1994
DOI: 10.1152/ajpheart.1994.267.4.h1608
|View full text |Cite
|
Sign up to set email alerts
|

Restraining effects of captopril on sympathetic excitatory responses in dogs: a spectral analysis approach

Abstract: This study was planned to clarify the effects of captopril administration on the autonomic control of the circulation in conscious dogs and in dynamic conditions using spectral analysis of R-R interval and systolic arterial pressure (SAP) variabilities. Changes in sympathovagal balance modulating the sinoatrial (SA) node were inferred, respectively, from the low (LFR-R)- and high-frequency (HFR-R) components of R-R variability; LFSAP furnished a marker of sympathetic vasomotor control. Increases in sympathetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…This is in keeping with the known predominant resting vagal tone in resting dogs (32). With the onset of mild left ventricular systolic and diastolic dysfunction, there were major decreases of total RRI power and HF RRI variability, suggesting a significant contribution of decreased parasympathetic nervous system modulation in early heart failure pathophysiology.…”
Section: Discussionsupporting
confidence: 85%
“…This is in keeping with the known predominant resting vagal tone in resting dogs (32). With the onset of mild left ventricular systolic and diastolic dysfunction, there were major decreases of total RRI power and HF RRI variability, suggesting a significant contribution of decreased parasympathetic nervous system modulation in early heart failure pathophysiology.…”
Section: Discussionsupporting
confidence: 85%
“…In the present experiments, the baseline power density spectrum of heart rate was characterized by a predominance of the HF parasympathetically mediated region. This is in keeping with the known predominant resting vagal tone in resting dogs (32). With the onset of mild left ventricular systolic and diastolic dysfunction, there were major decreases of total RRI power and HF RRI variability, suggesting a significant contri-bution of decreased parasympathetic nervous system modulation in early heart failure pathophysiology.…”
Section: Discussionsupporting
confidence: 85%
“…These adverse reactions are assumed to be related to reflex-mediated sympathoexcitation. Unlike these vasodilators, angiotensin-converting enzyme inhibitors have been documented to improve sympathovagal imbalance and to exert beneficial influences on hemodynamics and long-term clinical outcome in patients with chronic heart failure (6,28,31,32). Recently, several large clinical trials have demonstrated that direct interference with the sympathetic nervous system by using a ␤-blocker improves symptoms and cardiac function in patients with dilated cardiomyopathy (23,34).…”
Section: Autonomic Imbalance In Heart Failurementioning
confidence: 99%